THE DEMENTIA JOURNEY IN INDIAN COUNTRY: OPTIONS FOR A PUBLIC HEALTH RESPONSE. (11th November 2018) - Splaine, M
Abstract: Alzheimer's and other dementias are an emerging public health issue for tribal and Native communities. CDC data indicate 19% of American Indians/Alaska Natives (AI/AN) aged 45+ report experiencing confusion or memory loss that is getting worse; research indicates such "subjective cognitive decline" is a good predictor of future diagnosis of Alzheimer's and other dementias. Grounded in consultations with tribal and Native leaders, a new tool aims to seed development of promising practices by I/T/U health on challenges their communities are experiencing as a growing group of Elders and their caregivers journey with dementia. The tool has been developed in consultation with tribal leaders with support from the Centers for Disease Control and Prevention and in partnership with the International Association for Indigenous Aging.